2010
DOI: 10.18632/oncotarget.180
|View full text |Cite
|
Sign up to set email alerts
|

An Activating Transcription Factor 5-Mediated Survival Pathway as a Target for Cancer Therapy

Abstract: ABSTRACT:Genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Moreover ATF5 promotes proliferation of cerebral cortical neuroprogenitor cells and is required for terminal differentiation and survival of olfactory sensory neurons [ 22 ]. In addition several studies have previously demonstrated that ATF5 is highly expressed in a variety of tumors [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover ATF5 promotes proliferation of cerebral cortical neuroprogenitor cells and is required for terminal differentiation and survival of olfactory sensory neurons [ 22 ]. In addition several studies have previously demonstrated that ATF5 is highly expressed in a variety of tumors [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell lysates were made in ice-cold 1X RIPA buffer (MilliporeSigma) containing 1 mmol/L phenylmethylsulfonyl fluoride (MilliporeSigma) and protease inhibitor cocktail (MilliporeSigma; refs. 14 , 19 ). Cell lysates were sonicated for 10 seconds (three times), and the protein concentration of each sample was measured using the Bio-Rad Protein Assay.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperactivated Ras regulates many oncogenic pathways in several human cancers, including glioblastoma, the most infiltrating, aggressive, and poorly treated brain tumor. Huang et al synthesized apolipoprotein E3-reconstituted high-density lipoprotein (ApoE-rHDL) encapsulated calcium phosphate (CaP) nanoparticle core, named as CaP-rHDL [103], for tumor-targeting siRNA delivery, activating transcription factor-5 (ATF5), an overexpressed anti-apoptotic transcription factor in glioblastoma [104,105]. They investigated in vivo tumor-targeting efficiency of CaP-rHDL and its cellular uptake through micropinocytosis in intracranial C6 and GICs glioblastoma-bearing mice models, and observed an efficient delivery of ATF5 siRNA to Ras-activated brain cancer cells [103].…”
Section: Ras Pathwaymentioning
confidence: 99%